Program pembinaan Kesehatan komunitas dalam pencegahan HIV/AIDS: Tinjauan literatur dari empat artikel terbaru - Mira Azmi Agustina; Miftahul Falah S.kep.,Ns.,MSN.Ph.d (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
HIV/AIDS remains a major global health issue affecting Indonesia’s productive population. Community-based health development programs are among the key strategies for raising awareness and preventing HIV transmission. This literature review aims to evaluate the effectiveness of community empowerment and health education programs in improving knowledge and behavioral changes related to HIV/AIDS prevention. Four articles were analyzed using PRISMA 2020 guidelines. Results show that educational, participatory, and cross-sectoral collaboration approaches, including the Asset-Based Community Development (ABCD) method, effectively enhance public awareness and reduce risky behaviors. Community-based programs are proven to strengthen local capacity in HIV/AIDS prevention